Epidemiological Evidence for Inflammation in Cardiovascular Disease - Tracy, Russell P. (Thrombosis and Haemostasis, 1999)
Recent evidence from a wide variety of sources implicates inflammation in the process of atherosclerosis and, ultimately, clinical cardiovascular disease. As summarized recently by Ross,2 the biochemical and cell biological evidence clearly supports the position that inflammation is involved in all stages of atherosclerotic development including, but not limited to, oxidative damage,3,4 cell proliferation, and plaque development and destabilization.5 Coagulation, thrombosis, and fibrinolysis are also strongly associated with inflammation, as studies of sepsis6 and post-trauma acute phase reaction7 have demonstrated.These relationships are complex. Inflammatory responses are mediated through the cytokine pathway, at least initially, with the major proinflammatory cytokines being interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α). As an example, the generation of proinflammatory cytokines in the setting of sepsis is a powerful procoagulant,8 and several coagulation factors, such as fibrinogen and factor VIII, have been known to be acute phase reactants for some time.9 Recent studies with purified cytokines support these findings.10 However, coagulation and fibrinolysis themselves are inflammatory. The production of fibrin degradation products, as the end result of coagulation and fibrinolysis, causes the systemic elaboration of IL-6 (and the up-regulation of liver proteins, such as coagulation factors), which is, most likely, the mechanism by which the body counters consumption of factors.11 We have, therefore, a circular mechanism: inflammation begets coagulation which begets more inflammation. What keeps this process in check? At this point it is uncertain, but it seems reasonable to speculate that on the one hand the elaboration of anti-inflammatory cytokines, e.g., IL-10, play a major role in the inflammatory pathway,12 while on the other, the factors that down-regulate coagulation, such as activated protein C (APC), at least partly control the coagulation side.13Inflammation appears to be associated with atherothrombotic disease throughout the natural history of this process, from the early stages of fatty streak development, to the rupture of complex plaque with resultant coronary (or peripheral) artery occlusion. Smith et al and Kaplan and colleagues have shown that by-products of coagulation are present in atherosclerotic plaque, including fatty streaks,14-16 and we have recently shown that increasing IL-6 levels by weekly injection results in a several-fold increase in fatty lesion size in a murine model of early atherosclerosis.17 As discussed below, abundant evidence links inflammation with atherothrombotic disease in middle-aged populations, using markers ranging from IL-6 itself, to fibrinogen, C-reactive protein (CRP), albumin, and other acute phase proteins. These markers predict events over long periods, again supporting the position that inflammation is associated with all phases of atherothrombotic disease.Finally, in the elderly, where coronary atherosclerosis is common, inflammation markers are still predictive, but may be more closely linked in time to the events. We believe this is due to the association being driven by the thrombotic component, since atherosclerotic development has often reached an advanced stage. These associations reflect the “proximate pathophysiology” associated with advanced plaque becoming unstable. We believe that the timeframe involved is on the order of 6 to 18 months. We hypothesize that this is different from the “vulnerable plaque” described by Fuster,18 Davies,19 and others, since it concerns the exposure of proinflammatory and procoagulant components in older individuals, most likely from complex, advanced plaque, not the lipid-laden, thin-capped plaque of young middle-aged individuals.